Surface-modified lithium-manganese-rich single-crystal positive electrode material, preparation method thereof and secondary battery
The single crystal lithium-rich manganese positive electrode material is prepared by controlling the grinding and calcining conditions, and the surface is modified with inorganic ammonium salt to form a lithium-leading layer, solving the problem of poor kinetic performance of lithium-rich manganese single-crystal positive electrode material, achieving the improvement of high-rate performance, energy density and cycling performance, while simplifying the process and reducing costs.
Patent Information
- Application Number
- CN202411950206.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
The lithium-rich manganese single crystal positive electrode material has poor kinetic performance, especially the poor rate performance, which limits its fast charging application, and the single crystallization process is complex and environmentally friendly.
By controlling the conditions of grinding and calcining, a single crystal-rich manganese positive electrode material is prepared, and its surface is modified with inorganic ammonium salt to form a lithium-depleted layer, thereby improving the rate performance, energy density and cycling performance of the material.
The rate performance, energy density and cycling performance of lithium-rich manganese single crystal positive electrode material is significantly improved, and the problem of poor fast charging performance is overcome. At the same time, the process is simplified, the cost is reduced, and environmental friendliness is improved.
Smart Images

Figure CN119750666A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium battery materials, and in particular to a surface-modified lithium-manganese-rich single crystal positive electrode material and a preparation method thereof, and a secondary battery. Background Art
[0002] In recent years, the commercialization of lithium-ion batteries (LIBs) has achieved great success in the fields of 3C devices and electric vehicles. Currently, commercial lithium-ion batteries are generally based on LiCoO2, LiNi x Co y Mn 1-x-y O2 or LiFePO 4, The specific capacities are 200, 180-220 and 150 mAh / g respectively. The further improvement of the energy density of the next generation lithium-ion batteries is mainly limited by the specific capacity and energy density of the positive electrode materials.
[0003] Lithium-rich manganese-based oxide cathode materials refer to a series of ternary materials with excess lithium and excess manganese (usually manganese exceeds 50% of the total transition metal atomic ratio). The ultra-high specific capacity (>250mAh / g) and energy density (>900Wh / kg) of lithium-rich manganese cathode materials make them the most promising cathode materials for the next generation of lithium-ion batteries. However, the poor kinetic performance of lithium-rich manganese cathode materials, especially the poor rate performance, limits their fast charging applications; secondary particles are prone to cracking, resulting in more surface area exposure and battery side reactions, while limiting the rolling pressure, compaction density and volume energy density of the cathode pole piece. Studies in recent years have shown that single crystalization is an effective means to improve the volume energy density, cycle performance and thermal stability of layered oxide cathode materials. However, single crystal cathode materials also face the problem of poor kinetic performance. Therefore, the biggest challenge of lithium-rich manganese single crystal cathode materials is the poor rate performance and inability to perform high-power charging and discharging caused by their slow kinetic properties.
[0004] In addition, if the previous lithium-rich manganese single crystal positive electrode materials need to obtain higher capacity and normal rate performance, they need to be obtained by adding a large amount of flux and using molten salt for long-term heat preservation at high temperature. For example, the Chinese patent with publication number CN116143200A uses a co-precipitation precursor, a lithium source, and a molten salt mixture to obtain a single crystal lithium-rich manganese-based material with high compaction density by step-by-step lithium preparation, calcination, and suction filtration and washing. The single crystal structure is good and the performance is excellent, but the process is relatively complicated, and the molten salt method requires a large amount of additional flux, and it is highly corrosive to the sintering furnace and has poor environmental friendliness. The Chinese patent with publication number CN116623295A discloses a tantalum-zirconium co-doped cobalt-free lithium-rich manganese single crystal positive electrode material and its preparation method. The lithium-rich manganese single crystal positive electrode material is obtained by ball milling mixing and high-temperature sintering in one step. The process method is relatively simple, but the single crystal particle size is relatively small and the dispersion is poor. Since the current preparation methods of single-crystal lithium-rich manganese single crystal positive electrode materials cannot simultaneously meet the requirements of process simplicity and excellent performance, simple and effective preparation and modification methods are needed to improve the performance of single-crystal lithium-rich manganese-based positive electrode materials. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a surface-modified lithium-rich manganese single crystal positive electrode material and a preparation method thereof, and a secondary battery. The preparation method of the present invention first obtains a single crystal lithium-rich manganese positive electrode material by controlling the conditions of grinding and calcination, and then uses an inorganic ammonium salt to modify the surface of the positive electrode material so that a lithium-poor layer is formed on the surface of the material, thereby obtaining a surface-modified lithium-rich manganese single crystal positive electrode material with good rate performance, high energy density, and excellent cycle performance, which greatly improves the performance of the lithium-rich manganese single crystal positive electrode material with poor kinetic performance; in addition, the preparation process of the present invention is simple, the raw materials are easily available and the cost is low, and it has obvious prospects for promotion and practical application.
[0006] To this end, the first aspect of the present invention provides a method for preparing a surface-modified lithium-rich manganese single crystal positive electrode material, comprising the following steps:
[0007] The nickel-cobalt-manganese ternary raw material and lithium salt are mixed, ground and calcined once to obtain lithium-rich manganese single crystal positive electrode particles;
[0008] Dispersing the lithium-rich manganese single crystal positive electrode particles and the inorganic ammonium salt in a solvent, and performing a heat treatment to obtain ammonium salt-coated lithium-rich manganese single crystal positive electrode particles;
[0009] The ammonium salt-coated lithium-rich manganese single crystal positive electrode particles are subjected to secondary calcination and water immersion treatment to obtain the surface-modified lithium-rich manganese single crystal positive electrode material.
[0010] The preparation method provided by the present invention successfully produces a single-crystal lithium-manganese-rich material that is currently difficult to prepare in the industry by controlling the conditions of grinding treatment and primary calcination, and the obtained single crystal particles have good dispersibility and uniform particle size. The surface modification step of inorganic ammonium salt makes the rate performance, energy density and cycle performance of the lithium-rich manganese single crystal positive electrode material significantly improved, thereby overcoming the problem of poor fast charging performance of lithium-rich manganese materials and single crystal materials.
[0011] According to an embodiment of the present invention, the inorganic ammonium salt includes at least one of ammonium sulfate, ammonium hydrogen sulfate, ammonium borate, ammonium fluoride, ammonium phosphate, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate.
[0012] According to an embodiment of the present invention, the nickel-cobalt-manganese ternary raw material comprises nickel-cobalt-manganese salt carbonate Mn x Ni y Co z CO3, nickel-cobalt-manganese hydroxide Mn x Ni y Co z (OH)2, nickel cobalt manganese oxide Mn x Ni y Co z At least one of O;
[0013] Among them, x, y, and z independently satisfy:
[0014] 0.5≤x<1, 0≤y≤0.5, 0≤z≤0.5, x+y+z=1.
[0015] According to an embodiment of the present invention, the lithium salt includes at least one of lithium carbonate, lithium hydroxide, lithium nitrate, lithium oxalate, and lithium oxide.
[0016] According to an embodiment of the present invention, the ratio of the molar amount of lithium in the lithium salt to the total molar amount of metal elements in the nickel-cobalt-manganese ternary raw material is 1.3:(0-1), and the total molar amount of metal elements in the nickel-cobalt-manganese ternary raw material is not 0.
[0017] According to an embodiment of the present invention, the mass ratio of the inorganic ammonium salt to the lithium-rich manganese single crystal positive electrode particles is (0.05-0.3):1.
[0018] According to an embodiment of the present invention, the grinding process is performed for 10 hours to 30 hours.
[0019] According to an embodiment of the present invention, the temperature of the primary calcination is 900°C-1100°C.
[0020] According to an embodiment of the present invention, the time of the first calcination is 5h-20h.
[0021] According to an embodiment of the present invention, the temperature of the heating treatment is 60°C-90°C.
[0022] According to an embodiment of the present invention, the temperature of the secondary calcination is 300°C-600°C.
[0023] According to an embodiment of the present invention, the secondary calcination time is 5h-20h.
[0024] The second aspect of the present invention provides a surface-modified lithium-manganese-rich single crystal positive electrode material, and the surface-modified lithium-manganese-rich single crystal positive electrode material is obtained by the preparation method described in the first aspect.
[0025] The surface modified lithium-rich manganese single crystal positive electrode material prepared by the present invention has good particle dispersibility, uniform particle size, high energy density, good cycle performance, and good rate performance, thereby significantly improving the fast charging performance.
[0026] The third aspect of the present invention provides a secondary battery, which comprises the surface-modified lithium-rich manganese single crystal positive electrode material obtained according to the preparation method described in the first aspect or the surface-modified lithium-rich manganese single crystal positive electrode material described in the second aspect.
[0027] The lithium-rich manganese positive electrode material has high energy density and is a potential positive electrode material for the development of secondary batteries, but its rate performance is too poor, resulting in poor fast charging performance. Although simple single crystal treatment can improve its energy density, cycle performance and other properties, the single crystal material also has the problem of low rate performance. Therefore, since the surface-modified lithium-rich manganese single crystal positive electrode material prepared by the present invention has good energy density, cycle performance and rate performance at the same time, it overcomes the problem of poor fast charging performance, and the preparation method is simple, the raw materials are cheap and easy to obtain, and it does not pollute the environment, and has broad prospects in the actual industrial application of secondary batteries.
[0028] The beneficial effects of the present invention compared to the prior art are as follows:
[0029] (1) By controlling the conditions of grinding and calcination, a single-crystal lithium-manganese-rich positive electrode material, which is currently difficult to obtain, was successfully prepared. The obtained particle size is uniform and the particle dispersion is good, and the performance is better than the single crystal preparation method of the existing technology.
[0030] (2) Through surface modification with inorganic ammonium salts, the surface modified lithium-manganese-rich single crystal positive electrode material has high energy density, good cycle performance and good rate performance, which overcomes the problem of poor fast charging performance of lithium-manganese-rich materials and single crystal materials. The overall preparation method is simple and inexpensive, and has broad prospects in the practical application of secondary batteries.
[0031] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0033] Figure 1 The SEM images of the lithium-rich manganese single crystal positive electrode particles and the surface-modified lithium-rich manganese single crystal positive electrode materials prepared in Example 1 of the present invention are shown. Among them, Figure a is a SEM image of the lithium-rich manganese single crystal positive electrode particles prepared in Example 1; Figure b is a SEM image of the surface-modified lithium-rich manganese single crystal positive electrode material prepared in Example 1;
[0034] Figure 2 The first cycle charge-discharge curve of the surface-modified lithium-rich manganese single crystal positive electrode material prepared in Example 1 of the present invention is obtained with lithium metal as the negative electrode, a rate of 0.1C and a cut-off voltage of 2.0-4.8V;
[0035] Figure 3 The figure shows the rate performance test results of the surface modified lithium-rich manganese single crystal positive electrode material prepared in Example 1 of the present invention;
[0036] Figure 4 The fast charging performance test results of the surface-modified lithium-rich manganese single crystal positive electrode material prepared in Example 1 of the present invention are shown;
[0037] Figure 5 The long cycle discharge specific capacity test results of the surface modified lithium-rich manganese single crystal positive electrode material prepared in Example 1 of the present invention are shown;
[0038] Figure 6 The X-ray diffraction pattern of the surface-modified lithium-rich manganese single crystal positive electrode material prepared in Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0039] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0040] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0041] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0042] In order to make the present invention more easily understood, certain technical and scientific terms are specifically defined below. Unless otherwise clearly defined elsewhere in this document, all other technical and scientific terms used herein have the meanings commonly understood by those skilled in the art to which the present invention belongs.
[0043] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.
[0044] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequently described event or circumstance may but need not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.
[0045] According to an embodiment of the present invention, a first aspect of the present invention provides a method for preparing a surface-modified lithium-rich manganese single crystal positive electrode material, comprising the following steps:
[0046] (1) The nickel-cobalt-manganese ternary raw materials and lithium salt are mixed, ground and calcined once to obtain lithium-rich manganese single crystal positive electrode particles.
[0047] By controlling the conditions of the grinding process and the primary calcination, the obtained lithium-rich manganese material is a single-crystal particle with good dispersibility and uniform particle size. If the grinding process step in the preparation method is omitted, a positive electrode material with a single-crystal morphology cannot be obtained.
[0048] According to a specific embodiment of the present invention, the type of the nickel-cobalt-manganese ternary raw material is not particularly limited. As some specific examples, the nickel-cobalt-manganese ternary raw material includes nickel-cobalt-manganese salt carbonate Mn x Ni y Co z CO3, nickel-cobalt-manganese hydroxide Mn x Ni y Co z (OH)2, nickel cobalt manganese oxide Mn x Ni y Co z At least one of O;
[0049] Among them, x, y, and z independently satisfy:
[0050] 0.5≤x<1,0≤y≤0.5,0≤z≤0.5,x+y+z=1;
[0051] The value of x is not particularly limited. As some specific examples, the value of x may be 0.5, 0.6, 0.7, 0.8, 0.9, etc.;
[0052] The value of y is not particularly limited. As some specific examples, the value of y may be 0, 0.1, 0.2, 0.3, 0.4, 0.5, etc.;
[0053] The value of z is not particularly limited. As some specific examples, the value of z may be 0, 0.1, 0.2, 0.3, 0.4, 0.5, etc.
[0054] According to a specific embodiment of the present invention, the type of the lithium salt is not particularly limited. As some specific examples, the lithium salt includes at least one of lithium carbonate, lithium hydroxide, lithium nitrate, lithium oxalate, and lithium oxide.
[0055] According to a specific embodiment of the present invention, the ratio of the molar amount of lithium in the lithium salt to the total molar amount of metal elements in the nickel-cobalt-manganese ternary raw material is 1.3:(0-1), and the total molar amount of metal elements in the nickel-cobalt-manganese ternary raw material is not 0. As some specific examples, the ratio of the molar amount of lithium in the lithium salt to the total molar amount of metal elements in the nickel-cobalt-manganese ternary raw material may be 1.3:0.1, 1.3:0.3, 1.3:0.5, 1.3:0.8, 1.3:1, etc.
[0056] According to a specific embodiment of the present invention, the grinding process time is 10 hours to 30 hours. As some specific examples, the grinding process time can be 10 hours, 20 hours, 30 hours, etc.
[0057] According to a specific embodiment of the present invention, the temperature of the primary calcination is 900°C-1100°C. As some specific examples, the temperature of the primary calcination may be 900°C, 1000°C, 1100°C, etc.
[0058] According to a specific embodiment of the present invention, the time of the first calcination is 5h-20h. As some specific examples, the time of the first calcination can be 5h, 10h, 15h, 20h, etc.
[0059] According to a specific embodiment of the present invention, the grinding method is not particularly limited. As some specific examples, the grinding method includes but is not limited to a ball milling method or a grinding method without a grinding medium.
[0060] (2) Dispersing the lithium-rich manganese single crystal positive electrode particles and an inorganic ammonium salt in a solvent, and performing a heat treatment to obtain ammonium salt-coated lithium-rich manganese single crystal positive electrode particles.
[0061] After the lithium-manganese-rich single crystal positive electrode particles and the inorganic ammonium salt are dispersed in a solvent, heating and stirring are performed to gradually and completely evaporate the solvent, so that the ammonium salt is evenly coated on the surface of the lithium-manganese-rich single crystal positive electrode particles.
[0062] According to a specific embodiment of the present invention, the type of the inorganic ammonium salt is not particularly limited. As some specific examples, the inorganic ammonium salt includes at least one of ammonium sulfate, ammonium hydrogen sulfate, ammonium borate, ammonium fluoride, ammonium phosphate, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate.
[0063] According to a specific embodiment of the present invention, the mass ratio of the inorganic ammonium salt to the lithium-rich manganese single crystal positive electrode particles is (0.05-0.3):1. As some specific examples, the mass ratio of the inorganic ammonium salt to the lithium-rich manganese single crystal positive electrode particles may be 0.05:1, 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1, etc.
[0064] According to a specific embodiment of the present invention, the temperature of the heating treatment is 60°C-90°C. As some specific examples, the temperature of the heating treatment may be 60°C, 70°C, 80°C, 90°C, etc.
[0065] According to a specific embodiment of the present invention, the type of the solvent is not particularly limited. As some specific examples, the solvent includes but is not limited to pure water.
[0066] (3) The ammonium salt-coated lithium-rich manganese single crystal positive electrode particles are subjected to secondary calcination and water immersion treatment to obtain the surface-modified lithium-rich manganese single crystal positive electrode material.
[0067] During the secondary calcination process, the ammonium ions in the inorganic ammonium salt are decomposed by heat to volatilize into ammonia, while the non-volatile acid radicals react with the lithium ions in the lithium-rich manganese single crystal positive electrode particles to generate lithium salts, and at the same time a lithium-poor layer is constructed on the positive electrode surface. The thickness of the surface lithium-poor layer can be controlled by controlling the amount of inorganic ammonium salt, thereby regulating the performance of the material. The mixture is then soaked in water to dissolve the lithium salt, and the surface modified lithium-rich manganese single crystal positive electrode material can be obtained after washing.
[0068] According to a specific embodiment of the present invention, the temperature of the secondary calcination is 300°C-600°C. As some specific examples, the temperature of the secondary calcination may be 300°C, 400°C, 500°C, 600°C, etc.
[0069] According to a specific embodiment of the present invention, the time of the secondary calcination is 5 hours to 20 hours. As some specific examples, the time of the secondary calcination can be 5 hours, 10 hours, 15 hours, or 20 hours.
[0070] According to an embodiment of the present invention, a second aspect of the present invention provides a surface-modified lithium-manganese-rich single crystal positive electrode material, wherein the surface-modified lithium-manganese-rich single crystal positive electrode material is obtained by the preparation method described in the first aspect.
[0071] The surface modified lithium-rich manganese single crystal positive electrode material prepared by the present invention has the advantages of high capacity, high energy density, high rate performance, high dispersibility and high stability.
[0072] According to an embodiment of the present invention, the third aspect of the present invention provides a secondary battery, which comprises a surface-modified lithium-manganese-rich single crystal positive electrode material obtained according to the preparation method described in the first aspect or the surface-modified lithium-manganese-rich single crystal positive electrode material described in the second aspect.
[0073] The lithium-rich manganese positive electrode material has high energy density and is a potential positive electrode material for the development of secondary batteries, but its rate performance is too poor, resulting in poor fast charging performance. Although simple single crystal treatment can improve its energy density, cycle performance and other properties, the single crystal material also has the problem of low rate performance. Therefore, since the surface-modified lithium-rich manganese single crystal positive electrode material prepared by the present invention has good energy density, cycle performance and rate performance at the same time, it overcomes the problem of poor fast charging performance, and the preparation method is simple, the raw materials are cheap and easy to obtain, and it does not pollute the environment, and has broad prospects in the actual industrial application of secondary batteries.
[0074] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0075] Example 1
[0076] Take 5g Mn 0.6 Ni 0.2 Co 0.2 (OH)2 and 2g LiOH, where the molar ratio of lithium to the metal elements in the nickel-cobalt-manganese ternary raw material is 1.2:0.8, are added to a 100mL zirconia ball mill, and a zirconia ball mill is used as the ball milling medium. The ball mill is milled at 200rpm for 24h to obtain a uniform mixture. The mixture is then transferred to a corundum crucible, heated to 950℃ at a heating rate of 5℃ / min and kept warm for 10h, then naturally cooled to room temperature with the furnace and taken out to obtain a uniform black powder. After simple grinding in a mortar, the chemical formula is Li 1.2 Mn 0.48 Ni 0.16 Co 0.16O2-rich lithium manganese single crystal positive electrode particles. 1.2 Mn 0.48 Ni 0.16 Co 0.16 O2 is placed in a beaker, 60mL of pure water is added, and ultrasonic dispersion is performed for 30 minutes. Subsequently, 0.1g of ammonium sulfate is added, and after stirring to fully dissolve it, the beaker is placed on a heating table, the water temperature is controlled to 60°C, and magnetic stirring is performed at 300rpm until the water is completely evaporated to obtain a dark brown mixture. After taking out the mixture, it is further ground and mixed evenly using a mortar, and then placed in a corundum crucible, heated to 400°C at a heating rate of 5°C / min and calcined for 10 hours. After natural cooling, the mixture is washed three times with pure water using a centrifugal method to remove the soluble lithium sulfate on the surface. The obtained product is dried to obtain a surface-modified lithium-rich manganese single crystal positive electrode material.
[0077] The SEM images of the lithium-rich manganese single crystal positive electrode particles and the surface-modified lithium-rich manganese single crystal positive electrode materials obtained according to the above preparation method are shown in FIG. Figure 1 As shown, the surface modified lithium-rich manganese single crystal positive electrode material uses lithium metal as the negative electrode, with a rate of 0.1C and a cut-off voltage of 2.0-4.8V as the conditions, and the first cycle charge and discharge curve is as follows Figure 2 As shown, the rate performance of the surface modified lithium-rich manganese single crystal positive electrode material is as follows Figure 3 As shown in Figure 2, the fast charging performance of the surface modified lithium-rich manganese single crystal positive electrode material is as follows: Figure 4 As shown, the long cycle discharge specific capacity of the surface modified lithium-rich manganese single crystal positive electrode material is as follows Figure 5 As shown, the X-ray diffraction pattern of the surface modified lithium-rich manganese single crystal positive electrode material is as follows Figure 6 shown.
[0078] Depend on Figure 1-6 It can be seen that the surface modified lithium-rich manganese single crystal positive electrode material prepared in this embodiment has a typical single crystal morphology, and the particle diameter is about 800nm. The first cycle discharge capacity obtained by charging and discharging at a rate of 0.1C and a cut-off voltage of 2.0-4.8V is 266mAh g -1 , charged and discharged at a rate of 5C and a cut-off voltage of 2.0-4.8V, the discharge capacity is 179mAh g -1 After 200 cycles of charge and discharge at a rate of 0.5C and a cut-off voltage of 2.1-4.8V, the capacity retention rate was 93%.
[0079] Example 2
[0080] Take 5g Mn 0.6 Ni 0.2 Co 0.2(OH)2 and 2g LiOH, where the molar ratio of lithium to the metal elements in the nickel-cobalt-manganese ternary raw material is 1.2:0.8, are added to a 20mL polymer tank and mixed with a homogenizer at 2000rpm for 20 minutes to obtain a uniform mixture. The mixture is then transferred to a corundum crucible, heated to 950℃ at a heating rate of 5℃ / min and kept warm for 10h, then naturally cooled to room temperature with the furnace and taken out to obtain a uniform black powder. After simple grinding in a mortar, the chemical formula is Li 1.2 Mn 0.48 Ni 0.16 Co 0.16 O2-rich lithium manganese single crystal positive electrode particles. Afterwards, 2g Li 1.2 Mn 0.48 Ni 0.16 Co 0.16 O2 is placed in a beaker, 60mL of pure water is added, and ultrasonic dispersion is performed for 30 minutes. Subsequently, 0.1g of ammonium sulfate is added, and after stirring to fully dissolve it, the beaker is placed on a heating table, the water temperature is controlled to 60°C, and magnetic stirring is performed at 300rpm until the water is completely evaporated to obtain a dark brown mixture. After taking out the mixture, it is further ground and mixed evenly using a mortar, and then placed in a corundum crucible, heated to 400°C at a heating rate of 5°C / min and calcined for 10 hours. After natural cooling, the mixture is washed three times with pure water using a centrifugal method to remove the soluble lithium sulfate on the surface. The obtained product is dried to obtain a surface-modified lithium-rich manganese single crystal positive electrode material.
[0081] The surface modified lithium-rich manganese single crystal positive electrode material prepared in this example has a typical single crystal morphology, and the particle diameter is about 800nm. The first cycle discharge capacity obtained by charging and discharging at a rate of 0.1C and a cut-off voltage of 2.0-4.8V is 270mAh g -1 , charged and discharged at a rate of 5C and a cut-off voltage of 2.0-4.8V, the discharge capacity is 185mAh g -1 After 200 cycles of charge and discharge at a rate of 0.5C and a cut-off voltage of 2.1-4.8V, the capacity retention rate was 94%.
[0082] Example 3
[0083] Take 5g Mn 0.6 Ni 0.2 Co 0.2(OH)2 and 2g LiOH, where the molar ratio of lithium to the metal elements in the nickel-cobalt-manganese ternary raw material is 1.2:0.8, are added to the tank of a high-speed mixer and mixed at 500rpm for 30 minutes to obtain a uniform mixture. The mixture is then transferred to a corundum crucible, heated to 950℃ at a heating rate of 5℃ / min and kept at this temperature for 10h, then naturally cooled to room temperature with the furnace and taken out to obtain a uniform black powder. After simple grinding in a mortar, the chemical formula is Li 1.2 Mn 0.48 Ni 0.16 Co 0.16 O2-rich lithium manganese single crystal positive electrode particles. Afterwards, 2g Li 1.2 Mn 0.48 Ni 0.16 Co 0.16 O2 is placed in a beaker, 60mL of pure water is added, and ultrasonic dispersion is performed for 30 minutes. Subsequently, 0.1g of ammonium sulfate is added, and after stirring to fully dissolve it, the beaker is placed on a heating table, the water temperature is controlled to 60°C, and magnetic stirring is performed at 300rpm until the water is completely evaporated to obtain a dark brown mixture. After taking out the mixture, it is further ground and mixed evenly using a mortar, and then placed in a corundum crucible, heated to 400°C at a heating rate of 5°C / min and calcined for 10 hours. After natural cooling, the mixture is washed three times with pure water using a centrifugal method to remove the soluble lithium sulfate on the surface. The obtained product is dried to obtain a surface-modified lithium-rich manganese single crystal positive electrode material.
[0084] The surface modified lithium-rich manganese single crystal positive electrode material prepared in this example has a typical single crystal morphology, and the particle diameter is about 800nm. The first cycle discharge capacity obtained by charging and discharging at a rate of 0.1C and a cut-off voltage of 2.0-4.8V is 265mAh g -1 , charged and discharged at a rate of 5C and a cut-off voltage of 2.0-4.8V, the discharge capacity is 175mAh g -1 After 200 cycles of charge and discharge at a rate of 0.5C and a cut-off voltage of 2.1-4.8V, the capacity retention rate was 92%.
[0085] Example 4
[0086] Take 5g Mn 0.64 Ni 0.18 Co 0.18CO3 and 2.4g Li2CO3, where the molar ratio of lithium to the metal elements in the nickel-cobalt-manganese ternary raw material is 1.2:0.8, are added to a 100mL zirconia ball mill, and a zirconia ball mill is used as the ball milling medium. The ball mill is milled at 400rpm for 10 hours to obtain a uniform mixture. The mixture is then transferred to a corundum crucible, heated to 1050℃ at a heating rate of 5℃ / min and kept warm for 10 hours, then naturally cooled to room temperature with the furnace and taken out to obtain a uniform black powder. After simple grinding in a mortar, the chemical formula is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2-rich lithium manganese single crystal positive electrode particles. Afterwards, 2g Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2 is placed in a beaker, 60mL of pure water is added, and ultrasonic dispersion is performed for 30 minutes. Subsequently, 0.05g of ammonium phosphate is added, and after stirring to fully dissolve it, the beaker is placed on a heating table, the water temperature is controlled to 80°C, and magnetic stirring is performed at 300rpm until the water is completely evaporated to obtain a black mixture. After taking out the mixture, it is further ground and mixed evenly using a mortar, and then placed in a corundum crucible, heated to 400°C at a heating rate of 5°C / min and calcined for 10 hours. After natural cooling, the mixture is washed three times with pure water using a centrifugal method to remove the soluble lithium phosphate on the surface. After drying the obtained product, a surface-modified lithium-rich manganese single crystal positive electrode material is obtained.
[0087] The surface modified lithium-rich manganese single crystal positive electrode material prepared in this example has a typical single crystal morphology and a particle diameter of 1 μm. The first cycle discharge capacity obtained by charging and discharging at a rate of 0.1C and a cut-off voltage of 2.0-4.8V is 265 mAh g -1 , charged and discharged at a rate of 5C and a cut-off voltage of 2.0-4.8V, the discharge capacity is 170mAh g -1 After 200 cycles of charge and discharge at a rate of 0.5C and a cut-off voltage of 2.1-4.8V, the capacity retention rate was 92%.
[0088] Example 5
[0089] Take 5g Mn 0.75 Ni 0.25 Co 0.18CO3 and 2.4g Li2CO3, where the molar ratio of lithium to the metal elements in the nickel-cobalt-manganese ternary raw material is 1.2:0.8, are added to a 100mL zirconia ball mill, and a zirconia ball mill is used as the ball milling medium. The ball mill is milled at 400rpm for 10 hours to obtain a uniform mixture. The mixture is then transferred to a corundum crucible, heated to 1000℃ at a heating rate of 5℃ / min and kept warm for 10 hours, then naturally cooled to room temperature with the furnace and taken out to obtain a uniform black powder. After simple grinding in a mortar, the chemical formula is Li 1.2 Mn 0.6 Ni 0.2 O2-rich lithium manganese single crystal positive electrode particles. 1.2 Mn 0.6 Ni 0.2 O2 is placed in a beaker, 60mL of pure water is added, and ultrasonic dispersion is performed for 30 minutes. Subsequently, 0.2g of ammonium fluoride is added, and after stirring to fully dissolve it, the beaker is placed on a heating table, the water temperature is controlled to 90°C, and magnetic stirring is performed at 300rpm until the water is completely evaporated to obtain a black mixture. After taking out the mixture, it is further ground and mixed evenly using a mortar, and then placed in a corundum crucible, heated to 500°C at a heating rate of 5°C / min and calcined for 10 hours. After natural cooling, the mixture is washed three times with pure water using a centrifugal method. After drying the obtained product, a surface-modified lithium-rich manganese single crystal positive electrode material is obtained.
[0090] The surface modified lithium-rich manganese single crystal positive electrode material prepared in this example has a typical single crystal morphology and a particle diameter of 1 μm. The first cycle discharge capacity obtained by charging and discharging at a rate of 0.1C and a cut-off voltage of 2.0-4.8V is 252 mAh g -1 After 200 cycles of charge and discharge at a rate of 0.5C and a cut-off voltage of 2.1-4.8V, the capacity retention rate was 95%.
[0091] Comparative Example 1
[0092] Take 5g Mn 0.6 Ni 0.2 Co 0.2 (OH)2 was mixed with 2g LiOH to obtain a mixture in which the molar ratio of lithium to the metal elements in the nickel-cobalt-manganese ternary raw material was 1.2:0.8. The mixture was then transferred to a corundum crucible and heated to 950°C at a heating rate of 5°C / min for 10 hours. The mixture was then naturally cooled to room temperature and taken out to obtain a black powder. After simple grinding in a mortar, a chemical formula of Li 1.2 Mn 0.48 Ni 0.16 Co 0.16 O2-rich lithium manganese positive electrode particles. 1.2 Mn 0.48 Ni0.16 Co 0.16 O2 is placed in a beaker, 60mL of pure water is added, and ultrasonic dispersion is performed for 30 minutes. Subsequently, 0.1g of ammonium sulfate is added, and after stirring to fully dissolve it, the beaker is placed on a heating table, the water temperature is controlled to 60°C, and magnetic stirring is performed at 300rpm until the water is completely evaporated to obtain a dark brown mixture. After taking out the mixture, it is further ground and mixed using a mortar, and then placed in a corundum crucible, heated to 400°C at a heating rate of 5°C / min and calcined for 10 hours. After natural cooling, the mixture is washed three times with pure water using a centrifugal method to remove the soluble lithium sulfate on the surface. The obtained product is dried to obtain a surface-modified lithium-rich manganese positive electrode material.
[0093] The positive electrode material prepared in this comparative example has a polycrystalline morphology, and its charge and discharge properties are: after 200 cycles of charge and discharge at a rate of 0.5C and a cut-off voltage of 2.1-4.8V, the capacity retention rate is 83%. According to the results of this comparative example, when the grinding treatment step in the preparation method of the present invention is omitted, a positive electrode material with a single crystal morphology cannot be obtained, and its electrochemical performance will also deteriorate.
[0094] Comparative Example 2
[0095] The only difference between this comparative example and Example 1 is that ammonium molybdate is used instead of ammonium sulfate.
[0096] The positive electrode material prepared in this comparative example has a single crystal morphology, and its charge and discharge properties are: the first cycle discharge capacity obtained at a rate of 0.1C and a cut-off voltage of 2.0-4.8V is 220mAh g -1 , charged and discharged at a rate of 5C and a cut-off voltage of 2.0-4.8V, the discharge capacity is 100mAh g -1 , after 200 cycles of charge and discharge at a rate of 0.5C and a cut-off voltage of 2.1-4.8V, the capacity retention rate is 82%. Since lithium molybdate and molybdenum oxide and other substances exist on the surface of the positive electrode material after the secondary calcination in this comparative example, it can be seen from the discharge capacity at a rate of 5C and the capacity retention rate after 200 cycles of charge and discharge that the presence of molybdenum oxide and lithium molybdate on the surface of the positive electrode material will significantly reduce the electrochemical properties of the positive electrode material, such as rate performance, fast charging performance, and capacity retention. If you want to completely remove the water-soluble lithium molybdate and insoluble molybdenum oxide on the surface, you need to add processing steps in the preparation process, thereby increasing the complexity of the process.
[0097] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0098] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a surface-modified lithium-rich manganese single crystal positive electrode material, characterized in that: The following steps are involved: The nickel-cobalt-manganese ternary raw material and lithium salt are mixed, ground and calcined once to obtain lithium-rich manganese single crystal positive electrode particles; Dispersing the lithium-rich manganese single crystal positive electrode particles and the inorganic ammonium salt in a solvent, and performing a heat treatment to obtain ammonium salt-coated lithium-rich manganese single crystal positive electrode particles; The ammonium salt-coated lithium-rich manganese single crystal positive electrode particles are subjected to secondary calcination and water immersion treatment to obtain the surface-modified lithium-rich manganese single crystal positive electrode material.
2. The preparation method according to claim 1, characterized in that: The inorganic ammonium salt includes at least one of ammonium sulfate, ammonium hydrogen sulfate, ammonium borate, ammonium fluoride, ammonium phosphate, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate.
3. The preparation method according to claim 1, characterized in that: The nickel-cobalt-manganese ternary raw material includes nickel-cobalt-manganese salt carbonate Mn x Ni y Co z CO3, nickel-cobalt-manganese hydroxide Mn x Ni y Co z (OH)2, nickel cobalt manganese oxide Mn x Ni y Co z At least one of O; Among them, x, y, and z independently satisfy: 0.5≤x<1, 0≤y≤0.5, 0≤z≤0.5, x+y+z=1.
4. The preparation method according to claim 1, characterized in that: The lithium salt includes at least one of lithium carbonate, lithium hydroxide, lithium nitrate, lithium oxalate and lithium oxide.
5. The preparation method according to claim 1, characterized in that: The ratio of the molar amount of lithium in the lithium salt to the total molar amount of metal elements in the nickel-cobalt-manganese ternary raw material is 1.3:(0-1), and the total molar amount of metal elements in the nickel-cobalt-manganese ternary raw material is not zero.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the inorganic ammonium salt to the lithium-rich manganese single crystal positive electrode particles is (0.05-0.3):
1.
7. The preparation method according to claim 1, characterized in that: The grinding treatment time is 10h-30h.
8. The preparation method according to claim 1, characterized in that: The primary calcination temperature is 900°C-1100°C; Optionally, the primary calcination time is 5h-20h; Optionally, the temperature of the heating treatment is 60°C-90°C; Optionally, the temperature of the secondary calcination is 300°C-600°C; Optionally, the secondary calcination time is 5h-20h.
9. A surface-modified lithium-rich manganese single crystal positive electrode material, characterized in that: The surface modified lithium-manganese-rich single crystal positive electrode material is obtained by the preparation method according to any one of claims 1 to 8.
10. A secondary battery, characterized in that: The secondary battery comprises the surface-modified lithium-rich manganese single crystal positive electrode material obtained by the preparation method according to any one of claims 1 to 8 or the surface-modified lithium-rich manganese single crystal positive electrode material according to claim 9.
Citation Information
Patent Citations
High-compaction micron single crystal lithium-rich manganese-based positive electrode material, preparation method and lithium battery
CN116143200A
Tantalum and zirconium co-doped cobalt-free single crystal lithium-rich manganese-based positive electrode material and preparation method thereof
CN116623295A
Preparation method for surface-modified lithium-manganese-rich cathode material of lithium ion battery
CN104577101A
Preparation method of single-crystal high-nickel positive electrode material, product and application thereof
CN112520791A